Arches metallurgical study of clamp Brass and Model of prehispanic Inca settlement in the valley of Potrerillos - Carrizo, Silvana (2013)
Potrerillos Valley distant 50 km from the city of Mendoza, was in ancient times with the presence of man, as evidenced by the  scattered archaeological sites in the area. In a place called Blanco River no clear evidence importance due to a prolonged sequence of Indian occupation, primarily hunter-gatherers.Surveys in stratigraphy over 50 cm yielded no material of human origin and sources of supply of raw materials, which were dated  by radiocarbon  method 14 which ensures that the terrace was occupied from 600 BC to 1500 A.D. and the findings in this area are very valuable for reconstructing the past ten centuries of the history of pre-hispanic settlement in that region. The newest discovery in the area is an Inca clamp which corroborates the influence of the  Inca Empire from the Diamante River to northwest of Argentina. The Inca influence lasted about a hundred years. The study of dating agrees with the historical background since Mendoza was founded by Pedro del Castillo in 1561.